Dedicated Cold Snare vs. Traditional Snare for Polypectomy of Diminutive and Small Lesions in a Porcine Model: A Research Group for Endoscopic Instruments and Stents (REIS) Study - Han Hee Lee; Bo-In Lee; Jung-Wook Kim; Hyun Lim; Si Hyung Lee; Jun-Hyung Cho; Yunho Jung; Kyoung Oh Kim; Chan Gyoo Kim; Kee Myung Lee; Jong-Jae Park; Myung-Gyu Choi; et al. (Clinical Endoscopy, 2021)
Background/Aims The aim of this in vivo animal study was to evaluate the effectiveness and safety of dedicated cold snare (DCS) compared with those of traditional snare (TS) for cold snare polypectomy (CSP). Methods A total of 36 diminutive (5 mm) and 36 small (9 mm) pseudolesions were made by electrocoagulation in the colons of mini-pigs. Results For the diminutive lesions, there were no significant differences in technical success rate, procedure time, or complete resection rate between the DCS and TS groups; the rate of uneven resection margin in the DCS group was significantly lower than that of the TS group. For small lesions, technical success rate and complete resection rate were significantly higher in the DCS group than in the TS group (100% [18/18] vs. 55.6% [10/18], p=0.003; 94.4% [17/18] vs. 40% [4/10], p=0.006). In addition, the procedure duration was significantly shorter, and the rate of uneven resection margin was significantly lower in the DCS group (28.5 sec vs. 66.0 sec, p=0.006; 11.1% [2/18] vs. 100% [10/10], p<0.001). Two cases of perforation occurred in the DCS group. Multivariate analysis revealed that DCS use was independently associated with complete resection. Conclusions DCS is superior to TS in terms of technical success, complete resection, and reducing the duration of the procedure for CSP of small polyps.